Integrating Human Resource Management with Organizational Strategies (Global Journal of Management and Business Research, 2015)
The purpose of this article was to outline the benefits of integrating human resource development with organization strategies. It was to outline the perceived gap and show how the two are linked and how this link can contribute to organizational development.
Keywords: integration; organization strategies; strategy formulation; organizational development